Interactions between the sympathetic and sensory innervation of the iris - JA Kessler; W.O. Bell; IB Black (1983)
The interaction between peptidergic, sensory nerves and sympathetic fibers was examined in the rat iris. The putative peptide neurotransmitter, substance P, was used as an index of the sensory innervation, because the peptide is exclusively localized in the iris to trigeminal sensory fibers. Extirpation of the sympathetic, superior cervical ganglion resulted in an increase in iris content of substance P-like immunoreactivity (henceforth SP), suggesting that sympathetic terminals influence the peptidergic sensory innervation of the iris. The increase in iris peptide after sympathetic ganglionectomy was reversed by implantation of sympathetic ganglia into the anterior chamber of the eye. Pharmacological stimulation or blockade of sympathetic nerve impulse activity and pharmacological blockade of sympathetic axonal transport did not alter iris peptide, suggesting that these procedures did not mediate the sympathetic-sensory interaction. However, injection of nerve growth factor (NGF) systemically or into the anterior chamber increased iris peptide, reproducing the effects of ganglionectomy. Conversely, injection of antiserum to NGF (anti-NGF) into the anterior chamber decreased iris SP suggesting that endogenous trophic protein normally regulates sensory peptide. The effects of anti-NGF were transitory; iris peptide returned to normal after cessation of treatment. Consequently, anti-NGF administration apparently did not lead to sensory neuron destruction, but rather altered either the number of sensory fibers in the iris or the amount of peptide per fiber. Finally, injection of anti-NGF into the anterior chamber reversed the effects of sympathetic ganglionectomy, suggesting that NGF may mediate the sympathetic-sensory interaction. Our observations suggest that competition for target NGF may result in reciprocal regulation of the iris sympathetic and sensory innervation.